Facile fabrication of Ag decorated MnFeO3 catalyst: Comparative analysis of visible light driven antibiotic reduction and antibacterial performance - Karadirek, Seyda; Tuna, Ozlem; Simsek, Esra Bilgin; Altuntas, Seda; Cinar, Aycan Yigit (Academic Press Ltd- Elsevier Science Ltd, 2024)
Photocatalysis is an effective method with the potential to eliminate pharmaceutical compounds from water sources. Manganese ferrite (MnFeO3), a type of multiferroic perovskite catalyst, has attracted significant attention due to its small band gap, however its application was limited due to its high recombination rate and low quantum efficiency. It was therefore aimed to improve the properties of MnFeO3 by doping silver (Ag)-particles. In this study, Ag-MnFeO3 photocatalysts with different Ag content (1-3 mmol%) were synthesized by performing a facile hydrothermal method. The as-prepared samples were characterized using x-ray diffraction (XRD), scanning electron microscopy with energy-dispersive X-ray spectroscopy (SEM/EDS), transmission electron microscopy (TEM), x-ray photoelectron spectroscopy (XPS), ultraviolet-visible spectroscopy (DRS), photoluminescence spectroscopy (PL), electrochemical impedance spectroscopy (EIS) and Brunauer-Emmett-Teller (BET) method, showing successful addition of Ag-particles with the MnFeO3 structure. Then, the as-synthesized materials were investigated as: (i) photocatalysts for degradation tetracycline (TC) antibiotic and (ii) antibacterial agents for bacteria. The Ag-MnFeO3 catalyst demonstrated superior catalytic performance (95.7%), which was 1.6 times higher than that of pristine MnFeO3 (59.7%). The positive effect was ascribed to oxygen vacancies, enhanced light absorption ability, and lower recombination rate. The Ag-MnFeO3 catalyst also showed satisfactory removal performances in real water matrices. Furthermore, radical trapping tests depicted that the superoxide radicals played a dominant role in the photodegradation system. In addition, Box-Behnken design (BBD) was performed to determine the optimum conditions, which were determined as catalyst dosage of 0.45 g/L, initial TC concentration of 5.10 mg/L, and initial solution pH value of 3.69. In terms of antibacterial tests, the incorporation of Ag into the MnFeO3 structure greatly increased the antimicrobial resistance against bacteria. Our findings disclose that the incorporation of Ag into the MnFeO3 structure can be regarded as a feasible and promising approach to improve both photocatalytic degradation and antibacterial performances.
Keywords: MnFeO3; Tetracycline; Silver; Antibacterial; Photocatalyst